Report of High Level Team for Land Use Plan of Sikkim - Planning Commission (Planning Commission Government of India, 1981)
The High Level Team Report for Sikkim presents a comprehensive framework for sustainable land use planning and resource management in the ecologically diverse Eastern Himalayan state. With Sikkim’s challenging mountainous terrain, variable climate, and rich natural resources, the report emphasizes efficient utilization of agricultural land, forests, and water resources to balance ecological preservation with socio-economic development. Key recommendations include mixed farming practices, terrace cultivation, modernized irrigation systems, livestock improvement, and agroforestry, alongside conservation of mountain ecosystems and biodiversity. Soil and water conservation strategies, including bench terracing, contour cultivation, and engineered runoff control, are proposed to mitigate erosion and enhance productivity. The report also highlights the development of agro-based industries, responsible tourism, and marketing infrastructure to bolster economic resilience. Institutional mechanisms, including a State Land Use Board and participatory community involvement, are recommended for effective implementation. Overall, the report provides an integrated approach to promoting sustainable agriculture, ecosystem conservation, and rural development in Sikkim, serving as a model for similar northeastern hill regions.
Government of India Planning Commission New Delhi May, 1981
Keywords: Sikkim; Land Use Planning; Soil Conservation; Irrigation; Agriculture; Horticulture; Agroforestry; Livestock Management; Water Resources; Terrace Farming; Forest Management; Sustainable Development